2014
DOI: 10.1111/ejn.12629
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and expertise on tactile learning in humans

Abstract: Repetitive tactile stimulation is a well-established tool for inducing somatosensory cortical plasticity and changes in tactile perception. Previous studies have suggested that baseline performance determines the amount of stimulation-induced learning differently in specific populations. Older adults with lower baseline performance than young adults, but also experts, with higher baseline performance than non-experts of the same age, have been found to profit most from such interventions. This begs the questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
(111 reference statements)
1
12
1
Order By: Relevance
“…However, this should not be a prerequisite for directly using the directional information without building a mental representation of space. With respect to the vibrotactile stimulation itself, previous studies have found only minor age effects [27] in 60-years-old participants. With further increases in age, vibration intensity thresholds increase, possibly because pacinian corpuscles are affected [28]- [30].…”
Section: Transfer Of Findingsmentioning
confidence: 85%
“…However, this should not be a prerequisite for directly using the directional information without building a mental representation of space. With respect to the vibrotactile stimulation itself, previous studies have found only minor age effects [27] in 60-years-old participants. With further increases in age, vibration intensity thresholds increase, possibly because pacinian corpuscles are affected [28]- [30].…”
Section: Transfer Of Findingsmentioning
confidence: 85%
“…Significant expertise by intervention interaction was found. The learning effect for the group of experts by occupation was found to be stronger than for the novice controls [24]. The above findings suggest that experts are more susceptible to effects of tactile stimulation than novices and raises the question whether tDCS will produce such difference as well.…”
mentioning
confidence: 80%
“…Besides described effects of peripheral or brain stimulation on tactile performance, it has been well established that individual tactile sensitivity and perception at all ages strongly depends on accumulating effects of use or disuse [19], [20]. Particularly, extensive daily tactile stimulation as in musicians or blind Braille readers [21]- [23] or in professionals such as surgeons, opticians, or fine mechanics [24], may alter tactile perception and related somatosensory cortical representations. In one study, expertise was defined solely by occupation, where service employees such as office clerks formed the novices group and craftsmen such as goldsmiths, dentists and watch makers formed the experts group.…”
mentioning
confidence: 99%
“…For example, experts with high occupational use of the hands and fingers are found to experience stronger intervention-related improvement than non-experts after training on a tactile discrimination task (Reuter et al, 2014), supporting the idea that activity prior to the testing session influences responses to neuroplasticity inducing interventions. Future studies might try to account for the effects of prior experience and voluntary activity by manipulating the initial activity state of cells and synapses prior to neuroplasticity induction.…”
Section: Individual Variability In Responses To Plasticity-inducing Imentioning
confidence: 77%
“…Evidence does demonstrate, however, that metaplasticity may differ as a function of prior experience (Reuter et al, 2014;Rosenkranz et al, 2007). For example, experts with high occupational use of the hands and fingers are found to experience stronger intervention-related improvement than non-experts after training on a tactile discrimination task (Reuter et al, 2014), supporting the idea that activity prior to the testing session influences responses to neuroplasticity inducing interventions.…”
Section: Individual Variability In Responses To Plasticity-inducing Imentioning
confidence: 99%